Induction of labour for predicted macrosomia: study protocol for the 'Big Baby' randomised controlled trial. Issue 11 (11th November 2022) - Ewington, Lauren Jade; Gardosi, Jason; Lall, Ranjit; Underwood, Martin; Fisher, Joanne D; Wood, Sara; Griffin, Ryan; Harris, Kirsten; Bick, Debra; Booth, Katie; Brown, Jaclyn; Butler, Emily; et al.
Abstract : Introduction: Large-for-gestational age (LGA) fetuses have an increased risk of shoulder dystocia. This can lead to adverse neonatal outcomes and death. Early induction of labour in women with a fetus suspected to be macrosomic may mitigate the risk of shoulder dystocia. The Big Baby Trial aims to find if induction of labour at 38 +0 –38 +4 weeks' gestation, in pregnancies with suspected LGA fetuses, reduces the incidence of shoulder dystocia. Methods and analysis: The Big Baby Trial is a multicentre, prospective, individually randomised controlled trial of induction of labour at 38 +0 to 38 +4 weeks' gestation vs standard care as per each hospital trust (median gestation of delivery 39 +4 ) among women whose fetuses have an estimated fetal weight >90th customised centile according to ultrasound scan at 35 +0 to 38 +0 weeks' gestation. There is a parallel cohort study for women who decline randomisation because they opt for induction, expectant management or caesarean section. Up to 4000 women will be recruited and randomised to induction of labour or to standard care. The primary outcome is the incidence of shoulder dystocia; assessed by an independent expert group, blind to treatment allocation, from delivery records. Secondary outcomes include birth trauma, fractures, haemorrhage, caesarean section rate and length of inpatient stay. The main trial is ongoing, following an internal pilot study. A qualitative reporting, health economic evaluation and parallel process evaluation are included. Ethics and dissemination: The study received a favourable opinion from the South West—Cornwall and Plymouth Health Research Authority on 23/03/2018 (IRAS project ID 229163). Study results will be reported in the National Institute for Health Research journal library and published in an open access peer-reviewed journal. We will plan dissemination events for key stakeholders. Trial registration number: ISRCTN18229892 .